2022
DOI: 10.1021/acsami.2c17961
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Loaded Cationic Fluid Lipid Nanodiscs and Liposomes with Brush-Conformation PEG Chains Penetrate Breast Tumors and Trigger Caspase-3 Activation

Abstract: Novel approaches are required to address the urgent need to develop lipid-based carriers of paclitaxel (PTX) and other hydrophobic drugs for cancer chemotherapy. Carriers based on cationic liposomes (CLs) with fluid (i.e., chain-melted) membranes (e.g., EndoTAG-1) have shown promise in preclinical and late-stage clinical studies. Recent work found that the addition of a cone-shaped poly(ethylene glycol)-lipid (PEG-lipid) to PTX-loaded CLs (CLsPTX) promotes a transition to sterically stabilized, higher-curvatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
7
2
Order By: Relevance
“…For example, recent cell-based studies have shown that the small size and shape anisotropy of micellar discs enhance cell uptake of these vectors , because distinct additional endocytic pathways are available to them: nanodiscs were found to use macropinocytosis and microtubule-mediated endocytosis in addition to the typical clathrin- and caveolae-mediated endocytic pathways used by larger spherical lipid vectors . Consistent with these in vitro results, formulations of PTX-loaded coexisting nanometer-scale fluid lipid discs and vesicles showed tumor penetration and proapoptotic activity in vivo in a model of triple-negative breast cancer in immunocompetent mice …”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…For example, recent cell-based studies have shown that the small size and shape anisotropy of micellar discs enhance cell uptake of these vectors , because distinct additional endocytic pathways are available to them: nanodiscs were found to use macropinocytosis and microtubule-mediated endocytosis in addition to the typical clathrin- and caveolae-mediated endocytic pathways used by larger spherical lipid vectors . Consistent with these in vitro results, formulations of PTX-loaded coexisting nanometer-scale fluid lipid discs and vesicles showed tumor penetration and proapoptotic activity in vivo in a model of triple-negative breast cancer in immunocompetent mice …”
Section: Resultscontrasting
confidence: 86%
“…39 Consistent with these in vitro results, formulations of PTX-loaded coexisting nanometer-scale fluid lipid discs and vesicles showed tumor penetration and proapoptotic activity in vivo in a model of triple-negative breast cancer in immunocompetent mice. 38 It is important to point out that all lipid assemblies studied in the present work have membranes that were in the fluid state. This contrasts with previous studies that have characterized the structure and properties of solid lipid nanodiscs, 35,36,39,64 where the (charge-neutral or slightly anionic) assemblies of lipids with saturated tails form the chain-ordered "gel" phase 69 with very low chain mobility.…”
Section: ■ Results and Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…30,63,64 By counteracting the nonspecific adhesion due to van der Waals interactions, PEGylation opens the opportunity for targeting of NPs with targeting moieties such as antibodies and homing peptides. 65,66 These ligands either engage with the endocytosis or transcytosis receptors expressed on the BMEC surface (eg, transferrin, insulin, lactoferrin, and lipoprotein receptors), penetrate directly through cellular membranes (cell-penetrating peptides (CPP)), 65,67,68 or used mixed pathways for BBB penetration. NP-CPP conjugates were the first BBB-crossing NPs that did not compromise the integrity of the BBB.…”
Section: Strategies To Cross the Bbb And Drug Delivery Challengesmentioning
confidence: 99%
“…The authors concluded that augmented tumor penetration was contingent upon both the degree of PEGylation and concomitant particle size, as particles with 10 mol% PEG exhibited favorable results. [130] There are other works that have Addressing the challenge of efficient NP diffusion within the tumor stroma has been pursued through three strategies. First, the physicochemical properties of the NPs, comprising particle size and rigidity, have demonstrated improved access to intratumoral regions.…”
Section: Physicochemical and Mechanical Properties Of Nps That Influe...mentioning
confidence: 99%